Connecting Calcium-Based Nanomaterials and Cancer: From Diagnosis to Therapy - Shuang Bai; Yulu Lan; Shiying Fu; Hongwei Cheng; Zhixiang Lu; Gang Liu (Nano-Micro Letters, 2022)
Abstract As the indispensable second cellular messenger, calcium signaling is involved in the regulation of almost all physiological processes by activating specific target proteins. The importance of calcium ions (Ca2+) makes its “Janus nature” strictly regulated by its concentration. Abnormal regulation of calcium signals may cause some diseases; however, artificial regulation of calcium homeostasis in local lesions may also play a therapeutic role. “Calcium overload,” for example, is characterized by excessive enrichment of intracellular Ca2+, which irreversibly switches calcium signaling from “positive regulation” to “reverse destruction,” leading to cell death. However, this undesirable death could be defined as “calcicoptosis” to offer a novel approach for cancer treatment. Indeed, Ca2+ is involved in various cancer diagnostic and therapeutic events, including calcium overload-induced calcium homeostasis disorder, calcium channels dysregulation, mitochondrial dysfunction, calcium-associated immunoregulation, cell/vascular/tumor calcification, and calcification-mediated CT imaging. In parallel, the development of multifunctional calcium-based nanomaterials (e.g., calcium phosphate, calcium carbonate, calcium peroxide, and hydroxyapatite) is becoming abundantly available. This review will highlight the latest insights of the calcium-based nanomaterials, explain their application, and provide novel perspective. Identifying and characterizing new patterns of calcium-dependent signaling and exploiting the disease element linkage offer additional translational opportunities for cancer theranostics.